Evolving cognition of the JAK-STAT signaling pathway: autoimmune disorders and cancer - Xue, Chen; Yao, Qinfan; Gu, Xinyu; Shi, Qingmiao; Yuan, Xin; Chu, Qingfei; Bao, Zhengyi; Lu, Juan; Li, Lanjuan (Signal transduction and targeted therapy, 2023)
The Janus kinase (JAK) signal transducer and activator of transcription (JAK-STAT) pathway is an evolutionarily conserved mechanism of transmembrane signal transduction that enables cells to communicate with the exterior environment. Various cytokines, interferons, growth factors, and other specific molecules activate JAK-STAT signaling to drive a series of physiological and pathological processes, including proliferation, metabolism, immune response, inflammation, and malignancy. Dysregulated JAK-STAT signaling and related genetic mutations are strongly associated with immune activation and cancer progression. Insights into the structures and functions of the JAK-STAT pathway have led to the development and approval of diverse drugs for the clinical treatment of diseases. Currently, drugs have been developed to mainly target the JAK-STAT pathway and are commonly divided into three subtypes: cytokine or receptor antibodies, JAK inhibitors, and STAT inhibitors. And novel agents also continue to be developed and tested in preclinical and clinical studies. The effectiveness and safety of each kind of drug also warrant further scientific trials before put into being clinical applications. Here, we review the current understanding of the fundamental composition and function of the JAK-STAT signaling pathway. We also discuss advancements in the understanding of JAK-STAT–related pathogenic mechanisms; targeted JAK-STAT therapies for various diseases, especially immune disorders, and cancers; newly developed JAK inhibitors; and current challenges and directions in the field.